Communication skills training for radiation therapists: preparing patients for radiation therapy. Issue 4 (21st April 2016) - Halkett, Georgia; O'Connor, Moira; Aranda, Sanchia; Jefford, Michael; Merchant, Susan; York, Debra; Miller, Lisa; Schofield, Penelope
Abstract: Introduction: Patients sometimes present for radiation therapy with high levels of anxiety. Communication skills training may assist radiation therapists to conduct more effective consultations with patients prior to treatment planning and treatment commencement. The overall aim of our research is to examine the effectiveness of a preparatory programme 'RT Prepare' delivered by radiation therapists to reduce patient psychological distress. The purpose of this manuscript was to describe the communication skills workshops developed for radiation therapists and evaluate participants' feedback. Methods: Radiation therapists were invited to participate in two communication skills workshops run on the same day: (1) Consultation skills in radiation therapy and (2) Eliciting and responding to patients' emotional cues. Evaluation forms were completed. Radiation therapists' consultations with patients were then audio‐recorded and evaluated prior to providing a follow‐up workshop with participants. Results: Nine full day workshops were held. Sixty radiation therapists participated. Positive feedback was received for both workshops with 88% or more participants agreeing or strongly agreeing with all the statements about the different components of the two workshops. Radiation therapists highlighted participating in role play with an actor, discussing issues; receiving feedback; acquiring new skills and knowledge; watching others role play and practicing with checklist were their favourite aspects of the initial workshop. The follow‐up workshops provided radiation therapists with feedback on how they identified and addressed patients' psychological concerns; time spent with patients during consultations and the importance of finding private space for consultations. Conclusion: Communication skills training consisting of preparing patients for radiation therapy and eliciting and responding to emotional cues with follow‐up workshops has the potential to improve radiation therapists' interactions with patients undergoing radiation therapy. Further research is warranted, similar to the RT Prepare study, to determine whether patient anxiety can be reduced as a result of improving communication and information provision. Abstract : In this article, we describe the communication skills workshops developed for radiation therapists and evaluate participants' feedback. Sixty radiation therapists participated in two communication skills workshops: (1) Consultation skills in radiation therapy and (2) Eliciting and responding to patients' emotional cues. Positive feedback was received for both workshops.